Evolutionary Algorithm Tuned PID controller based NOSLLC-SC converter for PV Application - V. Mahesh and S.Saravanan (International Journal of Control and Automation, 2020)
The Photovoltaic (PV) system is more efficient and inherently safe when compared to other power generating technologies with larger life.  But PV energy source failed by achieving efficient power generation and gets disturbed over changing atmospheric circumstances. Hence, to overcome the above-mentioned drawback, an efficient evolutionary algorithm tuned PID controller based Negative Output Super-Lift Luo Converter (NOSLLC) using Sheppard-Taylor (S-T) topology has been developed for PV applications. This proposed converter produces efficient energy, higher output voltage with minimum duty ratio, and lower voltage (0.0187) with low settling time (0.02s). In addition to that Gey Wolf optimization algorithm operates within low oscillation of power under stable and varying conditions. Thus, the proposed system enhances maximum power generation under low radiation and various atmospheric conditions.